Development Of Iot System With Raspberry Pi For Switchgear Condition Monitoring - Fouzi, Muhammad Hafiz Azri Mohd (Universiti Sains Malaysia, 2017)
Partial discharge is common phenomenon of partial breakdown inside or across the insulation, confined to a small crack or void (inside the insulation) or over the surface that cannot be seen roughly with eyes. In order to prevent that happens, needs to do inspection and monitoring for safety of the personnel and also to keep the high voltage equipment in well care. For this project, the combination of raspberry pi and several sensors was using to do monitoring via online so that the information about any high voltage equipment will be send through a user email. The sound sensor will take part for detecting sound of sparking inside the switchgear while thermistor will take part for sensing the temperature increase when the partial discharge occur. This method will be apply and tested.